Development of E-Learning courseware for O-level Mathematics - Cia, Zhi Kai. (2012)
“Practice makes perfect”, this phrase correctly paints the strategy for most GCE O Level Mathematics/ Additional Mathematics examinees to outperform one another and obtain the best grades possible. School’s supply of worksheets is no longer sufficient for competitive students and more resources are often demanded by students to facilitate their learning process. This final year project aims to provide the students with easily accessible tools for them to practice and understand typical examination questions. A combination of the rising trend of web applications and usefulness of traditional worksheet generation give birth to this web application which allows the generation of printable worksheets which are accompanied with answers and guided solutions in a web environment. There are no questions databases and all the questions are generated from algorithms programmed in Java language. This ensures a steady supply of questions only limited by the range of numbers chosen by the user and not the quantity of pre-produced questions. There are a few commercial alternatives such as Kutasoftware’s worksheet generator that are designed to cater to the general student population for a fee. However, there are various features such as the generation of solutions which are lacking. The different platforms such as an offline desktop environment, which these alternatives require, do not provide easy access to the general student population. With the trends of fast internet access across all kind of devices, the project is being developed as a web application which can be accessed with only a web browser and an internet connection. This report contains details of the research of the related-industries, the technologies and tools used for development, the analysis and design of the web application, and also the discussion of the potential future extension of the current project scope.